ANALISIS KEPATUHAN IBU TERHADAP IMUNISASI DI MASA PANDEMIC COVID 19 DI KLINIK CAHAYA BUNDA - Kursiah Warti Ningsih; Dona Martilova; Ambiyar Ambiyar; Fadhilah Fadhilah (LPPM Universitas Abdurrab, 2021)
Increase someone's immunity actively against a disease, so that if one day exposed to the disease will not be sick or only experience minor illnesses need to be immunized. There are so many factors that influence it. As we know, that in society there are still different understandings about immunization, so there are still many babies and toddlers who do not get immunization services. The reasons given by parents regarding this were, among others, because their children were afraid of heat, were often sick, the family did not allow it, the place of immunization was far away, they did not know the place of immunization, and were busy / bothered, added to the current condition with the covid outbreak 19. Objective research is to find out how the mother's compliance with immunization during the pvidemic covid 19 at the Cahaya Bunda Clinic in Pekanbaru. All infants aged 0-12 months were 128 babies as samples with total sampling technique. Bivariate analysis using chi-square, 95% confidence level ((p = 0.05). From the results of the study found that the variables of maternal age, education, occupation, maternal anxiety, and family income towards maternal adherence to immunization during the pvidemic covid 19. It is expected that health workers will provide more education about the importance of immunization during the pandemic, but with covid prevention prevention health procedures 19.